2020
DOI: 10.21037/atm.2020.02.36
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic potential of GPX1 in human cancers based on data mining

Abstract: Background: Glutathione peroxidase-1 (GPX1) is a member of the GPX family, which considered an enzyme that interacts with oxidative stress. GPX1 differential expression is closely correlated with carcinogenesis and disease progression. In this study, we used bioinformatics analysis to investigate GPX1 expression level and explore the prognostic information in different human cancers. Methods: Expression was analyzed via the Oncomine database and Gene Expression Profiling InteractiveAnalysis tool, and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
(32 reference statements)
4
38
1
Order By: Relevance
“…Our study found that GPX1 gene expression tended to be elevated in most cancers, and the results of survival and tumor stemness analyses suggested that the GPX1 gene plays different roles in different types of cancer. This conclusion is consistent with previous findings, and so the role of the GPX1 gene in cancer might need to be analyzed while considering specific types of cancer in order to identify the underlying mechanism [ 57 ]. However, the GPX1 gene is definitely becoming more widely accepted as a potential biomarker for diagnosis and prognosis [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that GPX1 gene expression tended to be elevated in most cancers, and the results of survival and tumor stemness analyses suggested that the GPX1 gene plays different roles in different types of cancer. This conclusion is consistent with previous findings, and so the role of the GPX1 gene in cancer might need to be analyzed while considering specific types of cancer in order to identify the underlying mechanism [ 57 ]. However, the GPX1 gene is definitely becoming more widely accepted as a potential biomarker for diagnosis and prognosis [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion is consistent with previous findings, and so the role of the GPX1 gene in cancer might need to be analyzed while considering specific types of cancer in order to identify the underlying mechanism [ 57 ]. However, the GPX1 gene is definitely becoming more widely accepted as a potential biomarker for diagnosis and prognosis [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…Metascape ( http://metascape.org ) was used to perform functional enrichment analysis. This is an online analytical tool integrated with several ontology sources including the KEGG pathway, GO biological processes, Reactome gene sets, canonical pathways, and CORUM [ 17 ]. Pathway and process enrichment for each DEGs gene were analyzed for statistical significance in each biological process.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mRNA level of GPX1 and GPX4 decreased by a different degree in all three lymphomas cell lines. Wei et al [ 81 ] and Kinowaki et al [ 82 ] showed that GPX1 and GPX4 overexpression correlated with a poor prognosis in lymphoma patients and also inhibited ROS-induced cell death in vitro. Therefore, the decrease of both GPX1 and GPX4 gene expression indicated that the [Au(d2pype)2]Cl overcomes cell protection based on GPX and induces cell death.…”
Section: Discussionmentioning
confidence: 99%